P4.017 Queensland Agriculture, Forestry and Fishing Work Health and Safety Prosecutions: Repercussions. (14th March 2021) - King, Jemma C; Franklin, Richard C; McBain-Rigg, Kristin E; Leggat, Peter A
Abstract : Context: Agriculture, forestry and fishing industries are among the most dangerous industries in which to work, in Australia and internationally. Australia and its states & territories have robust work health and safety regulation, enforcement and prosecution systems outlined via Work Health and Safety (WHS) Acts (and Regulations), in Queensland the new regulations came into effect in 2011. The acts require employers to provide a safe place of work, to protect workers (via procedures and other mechanisms) and to train workers in matters relating to WHS. Process: In Queensland, details of WHS and electrical safety law breaches, against which a prosecution and conviction have occurred, are made publicly available. Analysis: A review of the agriculture, forestry and fishing prosecutions in this public registry was performed focused on incident type, industry and outcomes. Suggestions for system-related improvements are outlined. Outcomes: Since 2014 (at 27 February 2020), 33 prosecutions have been successfully brought against defendants of which a third were due to a death. Penalty costs ranged from 5k to 400k. The common injuries from the incidents included amputation, fractures and crush injuries. Prevention options will be discussed. Learning Outcomes: The public register exists to serve as a deterrent to others, concurrently discouraging non-compliance and promoting improvements in safety practices and systems. A key consideration when trying to promote safety practice and system improvements is to create meaningful change, whilst also balancing the onerous nature of change. This is particularly pertinent as many agriculture-related ventures in Queensland are small to medium sized enterprises.